2023
DOI: 10.1182/bloodadvances.2022008116
|View full text |Cite
|
Sign up to set email alerts
|

Sequential pembrolizumab and AVD are highly effective at any PD-L1 expression level in untreated Hodgkin lymphoma

Abstract: In a multicenter, phase II investigator-initiated trial of sequential pembrolizumab and AVD, nearly two-thirds of patients with untreated unfavorable or advanced stage classic Hodgkin Lymphoma (cHL) achieved PET-defined complete or near complete metabolic responses (CMR) following 3 doses of pembrolizumab monotherapy. Furthermore, all achieved CMR following 2 cycles of AVD chemotherapy and 100% of patients were alive without relapse at the time of initial publication. We now report long-term follow-up, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…This sustained outstanding disease control is in line with an interim NIVAHL analysis 6 and a smaller trial investigating sequential pembrolizumab and AVD in 30 patients with earlystage unfavorable and advanced-stage HL. 7 The primary goal of novel first-line HL treatments is achieving highest possible cure rates at minimal treatment-related morbidity. 8,9 All experimental treatments in this setting need to undergo rigorous testing to avoid compromising the unprecedented improvements of HL outcomes over the past few decades.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This sustained outstanding disease control is in line with an interim NIVAHL analysis 6 and a smaller trial investigating sequential pembrolizumab and AVD in 30 patients with earlystage unfavorable and advanced-stage HL. 7 The primary goal of novel first-line HL treatments is achieving highest possible cure rates at minimal treatment-related morbidity. 8,9 All experimental treatments in this setting need to undergo rigorous testing to avoid compromising the unprecedented improvements of HL outcomes over the past few decades.…”
Section: Discussionmentioning
confidence: 99%
“…This sustained outstanding disease control is in line with an interim NIVAHL analysis 6 and a smaller trial investigating sequential pembrolizumab and AVD in 30 patients with early-stage unfavorable and advanced-stage HL. 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new concept of "near CMR" with >90% reduction in MTV has been suggested as a more sensitive method of response to checkpoint inhibitors than CMR, given either sequentially or in combination with doxorubicin, vinblastine and darcarbazine (AVD) chemotherapy in first-line treatment of patients with HL. 62,63 The combination of emerging blood biomarkers as well as established risk factors with early PET scans, which may provide complementary information to monitor response is appealing. Kurtz et al 36 demonstrated that early molecular response after one or two cycles of treatment with circulating tumor DNA (ctDNA) in 217 patients with DLBCL and interim PET (in the subset of 66 patients who had early PET scans) were independent predictors of PFS and OS.…”
Section: Response Prediction During Treatmentmentioning
confidence: 99%
“…A recent phase II trial investigated for the first time pembrolizumab as upfront first-line treatment in a sequential scheme followed by AVD. After three cycles of pembrolizumab 37% of patients were in CR with all patients achieving at least a PR, including in advanced stages, after 2 cycles of AVD [ 113 ]. Long-term results confirmed excellent PFS and OS which remained both at 100% after three years from therapy [ 114 ].…”
Section: Management Of Relapsed/refractory Hodgkin Lymphomamentioning
confidence: 99%